Mythical Images in “The Seasons” by Kristijonas Donelaitis: the Grass - Razauskas, Dainius (Tautosakos darbai, 2015)
This article is a continuation in the series of works on the reflections of Lithuanian folklore and mythology in the classical poem “The Seasons” by Kristijonas Donelaitis, the famous 18th century Lithuanian author (see Razauskas 2014a: 32–44, 2014b, 2015: 9–14). Here, the focus is on the peculiar “grass mythology”, namely, the allegoric, symbolical, mythical traditional images related to grass (meadow, haymaking, etc.) found in the second part of the poem. First, the parallel between man and flower / plant is taken into consideration (lines 2.73–76, 94–95 of the poem). Further, attention is turned to the traditional image of the personified death (The Reaper) with a scythe (2.88–91, 440–447), and afterwards, the traditional parallel between war and haymaking is investigated (2.434–443). Finally, the image of the grass, herbs and meadows as a beard is approached (2.442–447). Every one of these topics is illustrated with considerable amount of examples from folklore and mythological sources of Lithuanians and other related peoples. The presented analysis leaves no doubts regarding the traditional nature of the images used by Donelaitis.
Keywords: -